Adaptation of the hypothalamus–pituitary–adrenal axis to daily repeated stress does not follow the rules of habituation: A new perspective. (September 2015) - Rabasa, Cristina; Gagliano, Humberto; Pastor-Ciurana, Jordi; Fuentes, Silvia; Belda, Xavier; Nadal, Roser; Armario, Antonio
Highlights: Reduced HPA response to daily repeated stress is not an habituation-like phenomenon. Nearly maximal HPA adaptation is found with one single exposure to severe stressors. The stronger the stressor the greater the maximal the adaptation of the HPA response. The longer the inter-stress interval the greater the adaptation of the HPA response. HPA adaptation to repeated stress might depend on the elaboration of safety signal. Abstract: Repeated exposure to a wide range of stressors differing in nature and intensity results in a reduced response of prototypical stress markers (i.e. plasma levels of ACTH and adrenaline) after an acute challenge with the same (homotypic) stressor. This reduction has been considered to be a habituation-like phenomenon. However, direct experimental evidence for this assumption is scarce. In the present work we demonstrate in adult male rats that adaptation of the hypothalamus–pituitary–adrenal (HPA) axis to repeated stress does not follow some of the critical rules of habituation. Briefly, adaptation was stronger and faster with more severe stressors, maximally observed even with a single exposure to severe stressors, extremely long-lasting, negatively related to the interval between the exposures and positively related to the length of daily exposure. We offer a new theoretical view to explain adaptation to daily repeated stress.